Andrographolide Exhibits Anticancer Activity against Breast Cancer Cells (MCF-7 and MDA-MB-231 Cells) through Suppressing Cell Proliferation and Inducing Cell Apoptosis via Inactivation of ER-α Receptor and PI3K/AKT/mTOR Signaling - Ruhainee Tohkayomatee; Somrudee Reabroi; Duangjai Tungmunnithum; Warisara Parichatikanond; Darawan Pinthong (Molecules, 2022)
Breast cancer is the most common cancer among women worldwide. Chemotherapy followed by endocrine therapy is the standard treatment strategy after surgery or radiotherapy. However, breast cancer is highly resistant to the treatments leading to the recurrence of breast cancer. As a result, the development of alternative medicines derived from natural plants with fewer side effects is being emphasized. Andrographolide isolated from Andrographis paniculata is one of the potential substances with anti-cancer properties in a variety of cell types, including breast cancer cells. This study aims to investigate the anti-cancer effects of andrographolide in breast cancer cells by evaluating cell viability and apoptosis as well as its underlying mechanisms through estrogen receptor (ER)-dependent and PI3K/AKT/mTOR signaling pathways. Cell viability, cell apoptosis, mRNA or miRNA, and protein expression were examined by MTT assay, Annexin V-FITC, qRT-PCR, and Western blot analysis, respectively. MCF-7 and MDA-MB-231 cell viability was reduced in a concentration- and time-dependent manner after andrographolide treatment. Moreover, andrographolide induced cell apoptosis in both MCF-7 and MDA-MB-231 cells by inhibiting Bcl-2 and enhancing Bax expression at both mRNA and protein levels. In MCF-7 cells, the ER-positive breast cancer, andrographolide showed an inhibitory effect on cell proliferation through downregulation of ERα, PI3K, and mTOR expression levels. Andrographolide also inhibited MDA-MB-231 breast cancer cell proliferation via induction of cell apoptosis. However, the inhibition of MCF-7 and MDA-MB-231 cell proliferation of andrographolide treatment did not disrupt miR-21. Our findings showed that andrographolide possesses an anti-estrogenic effect by suppressing cell proliferation in MCF-7 cells. The effects were comparable to those of the anticancer drug fulvestrant in MCF-7 cells. This study provides new insights into the anti-cancer effect of andrographolide on breast cancer and suggests andrographolide as a potential alternative from the natural plant for treating breast cancer types that are resistant to tamoxifen and fulvestrant.